Analisis Perputaran Persediaan Dalam Meningkatkan Profitabilitas Pada PT.Charoen Pokphand Indonesia Tbk - Yona Andreani; Muhammad Syahbudi; Nurlaila Nurlaila (Jurnal Akuntansi dan Keuangan, 2022)
Profitability is one of the tools used to see the financial performance of a company in generating profits. One of the assets that are directly related in generating profit is inventory. This study aims to analyze how inventory turnover increases company profitability as measured by Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Assets (ROA) and Return On Equity (ROE) at PT. Charoen Pokphand Indonesia Tbk. This research uses qualitative research with descriptive approach and secondary data sources. Based on the results of this study, it can be seen that inventory turnover has not been able to increase profitability at PT. Charoen Pokphand Indonesia Tbk. The decrease in inventory turnover was caused by the accumulation of inventory which illustrates the inefficient inventory management. The decrease in GPM was caused by an increase in the cost of goods sold and a decrease in the selling price of products. The decrease in NPM was caused by operating expenses and income taxes that were too large compared to the previous year as well as a decrease in revenue from sales. The decline in the value of ROA is due to ineffective asset management, this can be seen from the high number of company assets but low profits. The decrease in return or ROE indicates that the company is not effective in using the company's equity so that the increase in net income is smaller than the increase in company equity.